Analisis Perkiraan Biaya Ekonomi Deforestasi Di Kalimantan Barat - Yani, Akhmad (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2019)
Almost all forest areas in the districts / cities in West Kalimantan experience reduced area. Reducing the area of forest area or deforestation can, of course, have a detrimental impact on the environment which in turn can disrupt the sustainability of development itself. Deforestation has ecological, economic and social impacts. The higher the rate of deforestation, it will cause the potential impact will also increase. West Kalimantan experienced a fairly high level of deforestation. This gives an indication that the impact caused by deforestation in West Kalimantan has a relatively high potential. In other words, deforestation causes losses including economic losses. Related to this, the research question is how much economic value is the loss caused by deforestation in West Kalimantan? This research has 2 (two) objectives: first, calculating the economic costs of deforestation in West Kalimantan during the period 2009-2015, and second, analyzing the effect of the economic costs of deforestation on West Kalimantan's GDP during the period 2009-2015. Based on the data base for the period 2009 to 2015 and using the benefit transfer technique, this research has found that the highest economic losses occur in the secondary production forest and the lowest in the conservation forest area. Furthermore, during the period 2009 to 2015, this study has found that the highest economic loss value occurred in 2013 and the lowest occurred in 2011. Overall, the value of economic losses in the form of a combination of depletion and degradation provides a less significant reduction on the value of the forestry sub-sector GRDP in West Kalimantan.